The Ides Of March : Representasi Etos Kerja Seorang Public Relation - Alfath Yosiana Putri (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2019)
The film The Ides of March tells the work ethic of a public relations (PR). The purpose of this research is to find out the work ethic of PR practitioners in the film The Ides of March. This article is interpretive qualitative with the object of research is a PR on the film